POLA KOMUNIKASI INTERPERSONAL KEPALA MADRASAH (STUDI KASUS POLA KOMUNIKASI ANTARA KEPALA MADRASAH DAN GURU DI MTS NEGERI 1 BANDAR LAMPUNG) - Yenny Diahastaty, (UNISAN JURNAL, 2024)
This study aims to determine: 1) To find out the pattern of interpersonal communication between the Principal and the teacher verbally in MTS Negeri 1 Bandar Lampung , Ogan Komering Ulu Regency, South Sumatra Province, in the 2021/2022 academic year 2) To find out the pattern of interpersonal communication between the Principal and the teacher in writing at the MA. Asyifa Baturaja, Ogan Komering Ulu Regency, South Sumatra Province, for the 2021/2022 Academic Year. 3) To find out the effectiveness of the interpersonal communication pattern of the principal at MTS Negeri 1 Bandar Lampung , Ogan Komering Ulu Regency, South Sumatra Province This research is a descriptive study with a qualitative approach, with data sources from principals, and teachers at MTS Negeri 1 Bandar Lampung , Ogan Komering Ulu Regency, South Sumatra Province, for the 2021/2022 academic year. Researchers used the method of observation, interviews and documentation for data collection needed in this study. The data analysis technique used is interactive analysis which includes: data reduction, data presentation and conclusion drawing. From the results of the study, it is known that the pattern of interpersonal communication in MTS Negeri 1 Bandar Lampung , Ogan Komering Ulu Regency, South Sumatra Province, for the 2021/2022 academic year which includes: (1) Interpersonal communication patterns between the principal and teachers verbally at MTS Negeri 1 Bandar Lampung , Ogan Komering Ulu Regency, South Sumatra Province. The principal's verbal communication pattern is carried out face-to-face directly with the teacher, walking in one direction through greetings, direct directions both in meetings and in the daily work environment in an effort to improve teacher performance. (2) The communication pattern of the principal in writing is carried out through written means such as an official letter which is used to instruct teachers when there are routine meeting activities. In addition to official letters, written communications are also delivered using applications such as SMS, BBM and Whatsapp. (3) The effectiveness of the principal's interpersonal communication pattern at MTS Negeri 1 Bandar Lampung , Ogan Komering Ulu Regency, South Sumatra Province. Interpersonal communication carried out by the principal through the dimensions of effective interpersonal communication (openness, empathy, support, being positive/positive, equality, audible, and humble) has been running quite effectively. In terms of implementation, oral communication patterns are more effectively applied. This is because the pattern of oral communication is easier to understand, is open, there is reciprocity between the principal as the transmitter of communication to the teacher as the recipient of information